2015
DOI: 10.1016/j.ajem.2015.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of ED revisits and death among older adults after a fall

Abstract: Introduction Falls among older adults (aged ≥65 years) are the leading cause of both injury deaths and emergency department (ED) visits for trauma. We examine the characteristics and prevalence of older adult ED fallers as well as the recurrent ED visit and mortality rate. Methods This was a retrospective analysis of a cohort of elderly fall patients who presented to the ED between 2005 and 2011 at two urban, level-1 trauma, teaching hospitals with approximately 80,000-95,000 annual visits. We examined the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
80
3
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 24 publications
(30 reference statements)
7
80
3
8
Order By: Relevance
“…There are many risk factors for falls, including history of previous falls, polypharmacy, environment, and many patients with minor injuries are discharged from the emergency department (ED) without a complete falls risk assessment . Recent studies have shown that older adults with falls who presented to the ED had an increased frequency of ED revisits, especially those with head trauma …”
Section: Introductionmentioning
confidence: 99%
“…There are many risk factors for falls, including history of previous falls, polypharmacy, environment, and many patients with minor injuries are discharged from the emergency department (ED) without a complete falls risk assessment . Recent studies have shown that older adults with falls who presented to the ED had an increased frequency of ED revisits, especially those with head trauma …”
Section: Introductionmentioning
confidence: 99%
“…In the latter study, fall assessments were completed on average 5 to 10 weeks after the initial ED visit. Prompt evaluation and fall risk assessment, as can be done immediately after the injury in the ED, may prevent falls in the high‐risk immediate post‐fall period . The ED visit is an opportune time to initiate fall prevention measures because patients are optimally engaged, caregivers are often present, and hospital‐based staff, such as pharmacists and physical therapists (PTs), are available .…”
mentioning
confidence: 99%
“…20 While one previous study similarly sought to combine facility and provider claims to define ED visitation, our approach allows for repeat ED visitation within 72 hours, which have been shown to be common and were excluded by prior work. 2123 We therefore considered any hospital inpatient or outpatient claim for an ED visit on the same day, previous day, or following calendar day as an overlapping visit that should not be counted as a unique ED encounter (Table 1). Additionally, because providers or facilities claims may often include multiple ED visits on the same claim as a result of the claim adjudication and reporting processes, the number of ED visits captured by each definition can exceed the total number of claims.…”
Section: Methodsmentioning
confidence: 99%